Comparison of LQR and LQT Control of Uncertain Nonlinear Systems - Febri Setya Budi; Anggara Trisna Nugraha; Rama Arya Sobhita (Journal of Marine Electrical and Electronic Technology, 2025)
Optimal controls have been applied in this time. One of simple optimal control which will be analyzed in this research is planar arm model dynamic. Linear quadratic regulator (LQR) and linear quadratic tracker (LQT) are two well-known control techniques that have been widely applied in various fields such as engineering, robotics, and economics. LQR is a control method that aims to minimize the cost function of a linear system by adjusting the control input. On the other hand, LQT is a control technique that aims to track the reference input of a linear system while minimizing the cost function. Both LQR and LQT are optimal control methods that have good stability and performance characteristics. In this paper, we present a comparison of LQR and LQT control techniques and discuss their applications in various domains. We also highlight the advantages and limitations of these methods and suggest some possible future research directions.